Penyuluhan Pengelolaan Sampah Organik Rumah Tangga menjadi Pupuk Organik dengan Metode Takakura di Kecamatan Mallawa Maros - Haerul, Haerul; Mappiasse, Muh. Faisal; Hanafi, Muh. Alam Nasyrah (Universitas Nusantara PGRI Kediri, 2024)
Mallawa District is one of the areas that does not yet have a final waste disposal site so that people tend to dispose of waste indiscriminately. The purpose of community service is to provide knowledge to the community about how to process organic household waste into compost. The method used is in the form of lectures and demonstrations. The material presented was the management of organic waste into compost using Takakura baskets. The result of this community service activity is that participants consisting of members of farmer groups and housewives in three villages in Mallawa District can understand, be able to make and use Takakura baskets to process organic waste into compost.